Helping young German professionals to join international development organizations: opportunities, shortcomings and reform needs - Claus Burghard (Deutsches Institut für Entwicklungspolitik (DIE), 2003)
German public servants are not appropriately represented in many international organizations. With these organizations increasingly using internal promotion to fill their management posts, the Federal German Government should do more to help young professionals and change from a reactive to a proactive, strategically oriented personnel policy for Germans in international organizations. At the same time, the general conditions for returning professionals should be improved.Germany has enough high-quality undergraduate and post-graduate courses and internships to prepare young professionals for work in the development field, but they are not sufficiently geared to occupational integration.Many young professionals fail to take adequate account in their career planning of the need, given the very limited number of permanent posts in international organizations, so to structure their training that they also have job prospects in other institutions at home and abroadThe training provided by secondary schools and universities should be backed by the early provision of careers guidance. In this, schools and universities should cooperate closely with the Büro Führungskräfte zu Internationalen Organisationen (Office for Managers in International Organizations – BFIO) of the Zentralstelle der Arbeitsvermittlung (Central Employment Agency – ZAV).The instruments of Germany's international personnel policy at middle, higher and top management levels should be complemented by an instrument to promote the advancement of young professionals that follows on directly from the programme of Beigeordnete Sachverständige zu Internationalen Organisationen (Experts Assigned to International Organizations, or BS Programme, a Federal Government programme that assists young professionals).The BS Programme should be expanded. At the same time, Germans working in the United Nations (UN) agencies and European Union (EU) institutions should be linked more closely to Germany and familiarized with the German development agenda through the installation of counterpart structures in the relevant German government departments, through even closer attention from the Permanent Representatives and through the promotion of the development of networks.
Keywords: 330